1998
DOI: 10.1029/98jd00105
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotopic signatures (δ13C, δD) of methane from European landfill sites

Abstract: After formation of CH 4 its isotopic signature may be modified by secondary, isotope-fractionating processes. The most important of these processes is aerobic CH 4 oxidation by meth-8251

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
88
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 47 publications
16
88
0
1
Order By: Relevance
“…These results contrast with the context of a booming natural gas production and the resumption of coal mining in Asia. However, it is also worth noting that the 13 C / 12 C and D / H ratio of atmospheric methane show distinctive isotope signature depending on the source type (Bergamaschi, 1997;Bergamaschi et al, 1998;Quay et al, 1999;Whiticar and Schaefer, 2007). In the same way, isotopic fractionation occurs during sink processes with specific ratios depending on the removal pathway (Gierczak et al, 1997;Irion et al, 1996;Saueressig et al, 2001;Tyler et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These results contrast with the context of a booming natural gas production and the resumption of coal mining in Asia. However, it is also worth noting that the 13 C / 12 C and D / H ratio of atmospheric methane show distinctive isotope signature depending on the source type (Bergamaschi, 1997;Bergamaschi et al, 1998;Quay et al, 1999;Whiticar and Schaefer, 2007). In the same way, isotopic fractionation occurs during sink processes with specific ratios depending on the removal pathway (Gierczak et al, 1997;Irion et al, 1996;Saueressig et al, 2001;Tyler et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In air, the diffusion coefficient of 12 CH 4 exceeds that of 13 CH 4 by a factor of 1.0195 due to mass differences. No fractionation is expected when advection dominates gas transport (Bergamaschi et al, 1998;Chanton, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…4 -6 Field studies have shown that between 10 to 100% of the emitted methane can be oxidized on an annual basis. [7][8][9] Furthermore, methane flux emission measurements have shown negative fluxes, indicating uptake of atmospheric methane and proving that in some cases, landfill cover soils may even serve as sink for atmospheric methane. 10 -12 Although attenuation of methane in landfill covers has been intensively studied to evaluate the contribution of landfills to global warming, there is little research concerning the potential for attenuation of VOCs.…”
Section: Introductionmentioning
confidence: 99%